FORM OF PERFORMANCE OF THE FINAL SCENE IN THE BARONGAN DRAMATARY IN BLORA DISTRICT - Fifi Ester Galuh Cahyani; Eko Wahyuni Rahayu (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2024)
This research aims to describe the form of performance the Pentulan scene in the Barongan dance drama in Blora Regency. The form theory use by Schechner (2002)  dance drama theory used by Soedarsono and Narwati (2014) and Rusliana (2014) and function theory by Soedarsono (2001). The research method used is descriptive qualitative. Research data sources were obtained from person, place and paper data sources. Personal data: Adi Wibowo, Jaka Adi Kartika, Sofyan Said Maulana and Subur Widodo. Place data sources were obtained from observations at Sanggar Risang Guntur Seto (RGS) and performances in the Tempurejo village field. The paper data source was obtained from documentation in the form of photos and videos of performances. Data collection techniques use observation, interviews, documentation studies and literature studies. Data analysis techniques use data reduction, data presentation and drawing conclusions. Data validity uses method triangulation, source triangulation and method triangulation. The results of this research show that the performance form of the Pentulan scene consists of three parts, namely beginning, middle and end, whereas in the Barongan dance drama the Pentulan scene is in the middle part which uses the masked dance drama genre with a protagonist character.